The Implementation And Electrical Panel Maintenance Machine Enumerator Rubbish Plastic at TPSA Bagendung - Cilegon - Wirandi, Mohammad; Saputra, Deni; Silalahi, Radison; Supardi; Silalahi, Dianto (ANDAN JEJAMA: Indonesian Journal of Community Engagement (IJCE), 2025)
Waste is a very crucial problem if it is not addressed immediately. Waste that is not managed properly can pollute the environment, threaten human health, and disrupt the sustainability of the ecosystem. In the midst of the increasing amount of waste produced by society and industry, concrete and sustainable action is needed to manage it. The aim of this Community Service (PKM) activity was given to the Bagendung Cilegon Final Waste Management Site (TPSA) in the form of implementing and maintaining the electrical panel of the plastic waste shredding machine. This theme was chosen because we saw that the condition of the electrical panels at TPSA, especially the plastic chopping machines, still did not meet the electrical installation standards according to PUIL2000. So it is hoped that this theme can provide a solution for maintaining the electrical panel of plastic waste shredding machines according to PUIL 2000 standards